Imagining New York 2140 as an Urban Archipelago of Climate Futures and Alternative Modernities - Mohammed, Amrani; Isam, Mrah (Journal of Ecohumanism, 2026)
This article argues that Kim Stanley Robinson’s New York 2140 creates what this article calls the “accidental archipelago,” a broken and waterlogged city form that capitalism did not directly plan, but that its own excesses have unintentionally produced. Through this fragmented city, the novel creates spatial and social conditions where different forms of modern life become possible. Reading the novel through the connected ideas of the Capitalocene, critical island studies, speculative urbanism, and critical utopianism, the article makes three original contributions to existing scholarship on Robinson’s novel. First, the idea of the accidental archipelago adds to the language of island studies and climate fiction by naming an urban space created by climate change; this idea does not fit ordinary ideas of the city or the island. Second, the article argues that Robinson’s seven-narrator structure reflects this archipelagic logic in form: the novel itself becomes an archipelago of different voices that come together at the moment of political rupture, just as the debtors’ strike brings the plot to its end. Third, the article develops archipelagic utopianism as spatial rather than temporal, uncertain rather than fixed, and relational rather than sovereign, as a useful way of imagining politics in the Capitalocene.